Implementation of Experience Design on Museum Interiors. Case Study: East Java Cultural Museum - Allicia Sandra Meirissa; Titihan Sarihati; Vika Haristianti (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2021)
This study examines the involvement of interior design with the museum purpose in terms of education and recreation. The purpose of this study is to provide effective solutions in museum interior design to attract attention, education, and recreation to visitors and form the basis for future research. This research creates a design that forms a spatial experience, with a focus on cultural museums. The method used in this study is a qualitative method with three stages of triangulation (interviews, observations, and documents). The case study in this study is the East Java Cultural Museum because the phenomenon that occurs is that traditional culture has begun to erode due to the times, especially in East Java, and the absence of research on the interior design of cultural museums. This study shows that there are five aspects in supporting the creation of a visitor's space experience in the museum, including the atmosphere of the room, lighting, collection displays, storylines, and interactive media. These five aspects are united in an